Reinfection or Reactivation of Severe Acute Respiratory Syndrome Coronavirus 2: A Systematic Review - Tang, Xiujuan; Musa, Salihu S.; Zhao, Shi; He, Daihai (Frontiers in Public Health, 2021)
As the pandemic continues, re-detectable positive (RP) SARS-CoV-2 viral RNA scenarios among recovered COVID-19 patients raised public health concerns recently. It is imperative to investigate whether a re-detectable positive (RP) SARS-CoV-2 scenario can cause severe infection to the vulnerable population. In this work, we conducted a systematic review of the literature to investigate reactivation and reinfection in recovered COVID-19 patients that were found positive for the second time after recovery. Our study, consisting of more than 113,715 number of recruited patients, indicates that the RP-SARS-CoV-2 scenario occurs plausibly due to reactivation, reinfection, viral shedding, or testing errors and might cause outbreaks. Nonetheless, we observe that previously infected individuals have a significantly lower risk of being infected for the second time, indicating that reactivation or reinfection of SARS-CoV-2 has a relatively minimal impact in the overall population than the primary infection.